2019
DOI: 10.1186/s13104-019-4076-8
|View full text |Cite
|
Sign up to set email alerts
|

Yield of CT pulmonary angiography in the diagnosis of acute pulmonary embolism: short report

Abstract: ObjectiveTo assess computed tomography pulmonary angiography (CTPA) positive yield rate for pulmonary embolism (PE) in a Canadian academic tertiary center.ResultsThis one-center retrospective cross-sectional study includes from 5565 (model 1) to 5296 (model 2) patients that were evaluated for suspected PE in 2015, among which 1331 (23.9% (model 1) to 25.1% (model 2)) underwent CTPA. Mean age of CTPA patients was 60.2 ± 16.6 years, of which 575 were males (43.2%). Two hundred eleven CTPA examinations were posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…This compares to the yield of CTPA of inpatients, prior to the COVID-19 epidemic, of 12 to 17% [24][25][26], and 18% in an ICU environment [25]. Most literature on the use of CTPA centres on over-utilisation, particularly if yields fall below 10% [24][25][26]. The high-yield from CTPA in our series raises the possibility of relative under-diagnosis of PE in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This compares to the yield of CTPA of inpatients, prior to the COVID-19 epidemic, of 12 to 17% [24][25][26], and 18% in an ICU environment [25]. Most literature on the use of CTPA centres on over-utilisation, particularly if yields fall below 10% [24][25][26]. The high-yield from CTPA in our series raises the possibility of relative under-diagnosis of PE in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 54%
“…This study of hospitalised patients showed that in patients with suspected or confirmed COVID-19, and clinical suspicion for PE, more than one-third of CTPA studies were positive for PE. This compares to the yield of CTPA of inpatients, prior to the COVID-19 epidemic, of 12 to 17% [24][25][26], and 18% in an ICU environment [25]. Most literature on the use of CTPA centres on over-utilisation, particularly if yields fall below 10% [24][25][26].…”
Section: Discussionmentioning
confidence: 95%
“…In some cases these units even produced primary data and collaborated with researchers to cope with the lack of evidence in the scientific literature. [32][33][34][35] Many respondents supported that CSRs contained not enough data to support the decisional process and clinical practice. As a future avenue, it would be interesting to see if the opinion of the HTA units about the use of the CSRs has changed over the last 6 years.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a more recent prospective trial [ 4 ] that included 1814 patients from 12 hospitals, the diagnostic yield of CTPA for PE was shown to be 25%. In another retrospective study [ 5 ] done in a Canadian academic tertiary care center, a 15.9% positive rate for PE detection via CTPA was reported. In contrast to these previous studies, our study demonstrated a higher diagnostic yield of CTPA for PE.…”
Section: Discussionmentioning
confidence: 99%